2014
DOI: 10.4161/21597081.2014.980125
|View full text |Cite
|
Sign up to set email alerts
|

Niche-dependent genetic diversity in Antarctic metaviromes

Abstract: The metaviromes from 2 different Antarctic terrestrial soil niches have been analyzed. Both hypoliths (microbial assemblages beneath transluscent rocks) and surrounding open soils showed a high level diversity of tailed phages, viruses of algae and amoeba, and virophage sequences. Comparisons of other global metaviromes with the Antarctic libraries showed a niche-dependent clustering pattern, unrelated to the geographical origin of a given metavirome. Within the Antarctic open soil metavirome, a putative circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…50 °C mean annual temperature difference) and substantial spatial separation (approx. 55 degrees of latitude), suggesting that aridity and not temperature may be the dominant driver of host and viral diversity 22 , 65 . Interestingly, soil related metaviromes (from Kogelberg Biosphere Reserve fynbos soil, Peruvian rainforest soil and Antarctic Dry Valley desert soil) clustered together and were clearly distinct from soils which were geographically much closer.…”
Section: Resultsmentioning
confidence: 99%
“…50 °C mean annual temperature difference) and substantial spatial separation (approx. 55 degrees of latitude), suggesting that aridity and not temperature may be the dominant driver of host and viral diversity 22 , 65 . Interestingly, soil related metaviromes (from Kogelberg Biosphere Reserve fynbos soil, Peruvian rainforest soil and Antarctic Dry Valley desert soil) clustered together and were clearly distinct from soils which were geographically much closer.…”
Section: Resultsmentioning
confidence: 99%
“…Dinucleotide frequencies within metaviromes have shown distinct virus community clustering within single habitat types such as desert soils. Although reported from a single study which analyzed two sets of pooled samples, cluster analysis of hypolith and opensoil metaviromes from Antarctic and Namib Desert soil samples has shown that the two hypolith metaviromes clustered at a single node whereas, in contrast, the two open-soil metaviromes displayed identical patterns (65). Despite great geographic distances or differing environmental conditions, similar habitat types harbored more closely related viral communities.…”
Section: Factors Shaping Viral Community Structures In Desert Soilsmentioning
confidence: 99%
“…In addition, because particle yields are typically low, most soil virome studies have amplified extracted viral DNA using multiple displacement amplification, which renders the data sets both stochastically and systematically biased and nonquantitative ( 54 , 58 63 ). The few polar soil viromes have been from Antarctic soils and further demonstrated the genetic novelty of this gene pool while suggesting that resident viral communities were dominated by tailed viruses, had high habitat specificity, and were structured by pH ( 51 , 64 , 65 ).…”
Section: Introductionmentioning
confidence: 97%